One of us : conjoined twins and the future of normal - Dreger, Alice Domurat (Harvard University Press, 2004)
"One of Us views conjoined twinning and other "abnormalities" from the point of view of people living with these anatomies, and considers these issues within the larger historical context of anatomical politics. Anatomy matters, Alice Domurat Dreger tells us, because the senses we possess, the muscles we control, and the resources we require to keep our bodies alive limit and guide what we experience in any given context. Her thought-provoking and compassionate work exposes the breadth and depth of that context - the extent of the social frame upon which we construct the "normal." In doing so, the book calls into question assumptions about anatomy and normality, and transforms our understanding of how we are all intricately and inextricably joined."--Jacket.